Copyrightability of Java APIs Revisited. - Samuelson, Pamela (Communications of the ACM, 2015)
The article looks at U.S. copyright law pertaining to the application program interfaces (APIs) of computer programs. The author discusses the 2014 U.S. Court of Appeals (Federal Circuit) ruling in the case Oracle v. Google which held that software company Oracle's APIs for the Java programming language are entitled to copyright protection, a decision which she says is contrary to numerous precedents in recent years. She says the U.S. Supreme Court is deciding whether to grant Internet firm Google's request to review the case and expresses support for Google on the grounds that copyright protection for APIs would damage the interoperability of programs and potentially generate much further litigation.